Study on Ventilation System Linkage Control Strategy in a Double-Hole Tunnel Fire - Yizhou Zhuang; Hao Ding; Guoping Zheng; Youkai Cui; Yan Huang (Advances in Materials Science and Engineering)
In order to prevent smoke from flowing backward and penetrating into adjacent tunnel through cross channels during evacuation in case of fire accidents in highway tunnels, it is extremely necessary to implement the linkage control scheme for double-hole tunnel ventilation system. Therefore, six linkage control schemes for ventilation system are proposed in this article. Firstly, these six schemes were numerically simulated through Fire Dynamics Simulator (FDS) to obtain the flow velocity, flow direction, and smoke distribution under different schemes when the peak power of fire accidents is 30 MW. And two better schemes were selected for further investigation based on the evacuation conditions in the upper stream of fire source. Secondly, a 1 : 10 scale model experiment was conducted to test these two schemes, and the results from numerical simulation and model experiment were compared and verified. Finally, the location of fire accident, the time to develop stable opposite airflow, and the number of open cross channels were analyzed to confirm the applicability of the recommended scheme. The results show that the optimal scheme is to switch on the fans in the upstream of the fire accident and the fans on both sides of the cross channel in the non-fire tunnel to form positive pressure to control the smoke flow. This scheme ensures a stable and uniform smoke flow in the cross channel and personnel’s safety during evacuation.